The Effect of Surface Functionalization of Magnesium Alloy on Degradability, Bioactivity, Cytotoxicity, and Antibiofilm Activity - Morena Nocchetti; Michela Piccinini; Donatella Pietrella; Cinzia Antognelli; Maurizio Ricci; Alessandro Di Michele; Layla Jalaoui; Valeria Ambrogi (Journal of Functional Biomaterials)
Magnesium alloys are promising biomaterials to be used as temporary implants due to their biocompatibility and biodegradability. The main limitation in the use of these alloys is their rapid biodegradation. Moreover, the risk of microbial infections, often following the implant surgery and hard to eradicate, is another challenge. Thus, with the aim of reducing biodegradability and conferring antibiofilm activity, sheets of the magnesium alloy AZ31 were properly modified with the introduction of hydroxy (polyethyleneoxy)propyl silane (PEG) and quaternary ammonium silane chains (QAS). The derivatized sheets were characterized by ATR-FTIR spectroscopy and their performances as concerns their stability, Mg2+ in vitro release, and in vitro bioactivity were evaluated as well. The results showed an increased stability with a reduction in corrosion, a slower Mg2+ ion release, and the formation of hydroxyapatite in the sheets’ surface. In addition, cytotoxicity evaluations were carried out on human gingival fibroblasts showing that the AZ31 and AZ31-PEG plates had good cytocompatibility. Finally, the antibiofilm activity on Staphylococcus aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa was carried out by evaluating the capacity of inhibition of biofilm adhesion and formation. The results demonstrated a significant reduction in biofilm formation by Staphylococcus epidermidis on AZ31-QAS.